Prevalence and factors associated with anxiety during the COVID-19 pandemic among Malaysians: a cross-sectional study - SA, Bono; CS, Siau; Al, Samy; BS, Chua; M, Fitriana; Wl, Cheah; LS, Law; Vighnarajah,; WY, Low (Penerbit Universiti Kebangsaan Malaysia, 2023)
The COVID-19 pandemic is a significant public health threat with wide-reaching psychological implications. The drastic changes in lifestyle due to the implementation of the movement control order (MCO) were associated with adverse effects on mental health. This study aimed to examine the prevalence of anxiety among Malaysians during the COVID-19 pandemic and its associated factors. The following questionnaires were self-administered online through google form which included: (i) Generalised Anxiety Disorder-7; (ii) Short Boredom Proneness Scale; (iii) Short Scale for Measuring Loneliness in Large Surveys; and (iv) The World Health Organisation (WHO) well-being index. Higher scores denoted higher levels of anxiety, boredom, loneliness, and well-being. Out of the 543 participants, more than half (55.2%) reported mild (25.6%), moderate (13.8%) to severe (19.8%) anxiety. Multiple logistic regression showed higher odds of moderate to severe anxiety were reported among those divorced/separated/widowed (aOR 6.778, 95% CI [1.200, 38.296]), adults aged 25 to 34 years (aOR 2.038, 95% CI [1.049, 3.958]), 35 to 44 years (aOR 2.279, 95% CI [1.064, 4.882]), and with higher boredom levels (aOR 1.063, 95% CI [1.035, 1.092]). One in five Malaysians surveyed experienced severe anxiety. Adults within the working age range (between 25 and 44 years old) were at higher odds of having anxiety. Boredom increased the odds of anxiety compared to loneliness, well-being and coping. Thus, addressing the risk factors through public health messages is deemed important.